Study of hypertensive subjects with diabetes as co-morbidity - Salagre, Santosh B.; Itolikar, Shobha M.; Bhagwat, Suyog N. (International Journal of Research in Medical Sciences, 2017)
Background: Combined presence of diabetes and hypertension increases the chances of various complications manifold than individually. Together, they accelerate the development of left ventricular hypertrophy, coronary artery disease, renal dysfunction, diabetic retinopathy and cerebrovascular diseases. Methods: After ethical considerations this observational study was carried out to identify the clinical, laboratory and end-organ profile of Hypertensive subjects who also had Diabetes; this cohort was also compared with subjects who had hypertension only. Results: The prevalence of hypertensive subjects with diabetes as co-morbidity was 10.26%. 26.4% subjects had family history of diabetes and 20.4% had family history of hypertension. The mean diastolic blood pressure (83.66±12.0) was significantly higher in hypertensive diabetes group, than the subjects with hypertension only (76.98±6.46) and the difference was statistically significant (p <0.0001). 51.9% of hypertensive females with diabetes had significantly higher (p 0.0003) central obesity. Macrovascular damage was slightly more common in females and microvascular damage was common in male hypertensive diabetic subjects. Out of 102 patients having end organ damage 37.25% had single organ involvement and 62.75% had multiple organ involvement. Retinopathy (33.2%) was commonest followed by renal (27.6%), cardiovascular (16.2%) and cerebrovascular (14.8%). Hypertensive diabetic patients had higher occurrence of end organ damage reflecting the impact of diabetes-hypertension co-morbidity on target organs. Conclusions: Given the increasing rates of coronary artery disease among Indians, especially at a younger age, 5understanding and successfully managing this deadly duo may hold the key to reducing cardiovascular mortality in India.